2021
DOI: 10.1155/2021/1607475
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity and Hypertension: A Cohort Study in China

Abstract: The prevalence of general and central obesity has increased rapidly in China for decades, while little is known on obesity-normal weight-central obesity (NWCO) in China. In this study, we aim to depict the trend of the three kinds of obesity and to explore their associations with hypertension in a cohort study in China. We used data from eight waves of the China Health and Nutrition Survey (CHNS) in 1993, 1997, 2000, 2004, 2006, 2009, 2011, and 2015 for analysis. The Cochran–Armitage test was used for trend of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Besides these, central obesity was also related to a reduction in quality of life and an increment in health expenses. As the incidence of central obesity raised rapidly during recent years (7,25), several studies indicated a higher proportion of central obesity among females than males (6,8), which could be attributed to fertility and decreased estrogen levels. The relationship between obesity and hypertension was well-studied.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these, central obesity was also related to a reduction in quality of life and an increment in health expenses. As the incidence of central obesity raised rapidly during recent years (7,25), several studies indicated a higher proportion of central obesity among females than males (6,8), which could be attributed to fertility and decreased estrogen levels. The relationship between obesity and hypertension was well-studied.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Another study recruited 20,995 adults with high risk of CVD (72.6% had a history of stroke and 88.4% had hypertension) and followed them up for an average of 4.74 years. [10] A total of 4172 participants died during the trial. The incidence rate of fatal and non-fatal stroke was reduced by 14% with the salt substitute than with regular salt (RR = 0.86, 95% CI: 0.77-0.96, P = 0.006), as were the rates of MACE by 13% (RR = 0.87, 95% CI: 0.80-0.94, P < 0.001) and death by 12% (RR = 0.88, 95% CI: 0.82-0.95, P < 0.001).…”
Section: Risk Factors For Hypertensionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 28, 2023. ; https://doi.org/10.1101/2023.01. 27.23285091 doi: medRxiv preprint 4 communicable diseases [12]. Globally, 1.9 billion adults are obese, and 462 million are underweight [6].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Being Underweight can be defined as a low intake of nutrients, while obesity is the over-accumulation of fats. These abnormalities can act as a risk factor for non-4 communicable diseases [12]. Globally, 1.9 billion adults are obese, and 462 million are underweight [6].…”
mentioning
confidence: 99%